2015
DOI: 10.4141/cjss-2014-035
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus forms and response to changes in pH in acid-sensitive soils on the Precambrian Shield

Abstract: Baker, S. R., Watmough, S. A. and Eimers, M. C. 2015. Phosphorus forms and response to changes in pH in acid-sensitive soils on the Precambrian Shield. Can. J. Soil Sci. 95: 95Á108. Soil acidification may explain declines in total phosphorus (TP) levels that have been observed in surface waters in central Ontario, Canada, but much of the research on phosphorus (P) mobility in pH manipulated soils has been performed at high P concentrations (i.e., !500 mM). This study investigated P fractionation in acidic (pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The newly converted managed CAFD had uniform q max , with a depth similar to the mineral horizons of the forested CAFD soils. Acid soils were reported to have a high q max due to conditions that create high P affinities, such as the presence of Al and Fe hydroxy(oxides) on clay surfaces creating larger surface areas and strong bonding energies favoring Al and Fe phosphate precipitation (Baker et al., 2015; Eriksson et al., 2016; Olsen & Watanabe, 1957). The distinct q max of the LFH at the SJRDC forested locations was surprising; the literature also has contradictory opinions on the role of SOM (47.2% for forested SJRDC; Table 2) (Väänänen et al., 2007; Yang et al., 2019), especially in the presence of Al and Fe.…”
Section: Resultsmentioning
confidence: 99%
“…The newly converted managed CAFD had uniform q max , with a depth similar to the mineral horizons of the forested CAFD soils. Acid soils were reported to have a high q max due to conditions that create high P affinities, such as the presence of Al and Fe hydroxy(oxides) on clay surfaces creating larger surface areas and strong bonding energies favoring Al and Fe phosphate precipitation (Baker et al., 2015; Eriksson et al., 2016; Olsen & Watanabe, 1957). The distinct q max of the LFH at the SJRDC forested locations was surprising; the literature also has contradictory opinions on the role of SOM (47.2% for forested SJRDC; Table 2) (Väänänen et al., 2007; Yang et al., 2019), especially in the presence of Al and Fe.…”
Section: Resultsmentioning
confidence: 99%
“…Atmospheric inputs to the lakes were not altered, as these organic inputs are considered part of the lake P-load. Initial soil P concentrations were based on values measured by Baker (2014), and soil equilibrium coefficients based on laboratory derived equilibrium P concentrations (EPC 0 ) and Freundlich isotherm values for different soil and land use types (Peltovuori 2006;Väänänen 2008; Koski-Vähälä 2001).…”
Section: Inca-p Model Calibrationmentioning
confidence: 99%
“…Soils within south-central Ontario have also been subject to acidification, due to atmospheric deposition of H 2 SO 4 and HNO 3 . In soils with a relatively low pH, such as those overlying the Precambrian Shield, it has been suggested that sulphate (SO 4 2-) has a significant influence on P sorption, where competition between SO 4 2and P leads to lower P retention (Geelhoed et al 1997;Baker et al 2015). It is unlikely that SO 4 2has been the sole cause of P alterations at all sites, given a weak correlation between SO 4 2and P (Eimers et al 2009), and the large differences in rates of P declines between catchments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And although it is well documented that northern Sweden never reached a state of chronic acidification (Bishop et al 2000), the KCS sub‐catchments remain naturally acidic throughout the year (pH range from 4.4 to 6.6) and pH does not show any statistically significant recovery trend ( p > 0.05) for the period. However, there is still a discrepancy among studies on the relationship between pH, P sorption, and declines in surface water P concentration as both positive (Baker et al 2015) and negative (McDowell et al 2002) relationships have been reported in acidic solutions. In the end, a combination of lower rates of biological mineralization, increased activation of Al and Fe sinks, and reduced competition with sulfate for adsorption (McDowell et al 2002; Giesler et al 2005) could all have an impact on P retention in soils, with consequences for DIP supply to streams.…”
Section: Discussionmentioning
confidence: 99%